2010
DOI: 10.1007/s00330-010-1969-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional cardiac MR imaging with true fast imaging with steady-state free precession before and after intravenous injection of contrast medium: comparison of image quality and accuracy

Abstract: Cine SSFP can be obtained after injection of contrast medium without loss of accuracy for regional and global LV ventricular function. This protocol can be used to decrease imaging time for thorough cardiac examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It has already been suggested to take advantage of this impregnation time to acquire the cine images, so as to shorten the total examination time. If at 1.5T, some authors [ 15 , 16 ] have demonstrated that LV delineation remains accurate enough to correctly assess wall motion and LVEF, it has not yet been proven that b-TFE cine sequences obtained at 3T could be acquired after gadolinium injection, all the more since the difference in T1 between the blood pool and the myocardium is decreased when increasing the field strength [ 16 ]. If post-contrast is currently a common practice in many 1.5T CMR sites, its generalization to 3T sites is not yet supported by the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been suggested to take advantage of this impregnation time to acquire the cine images, so as to shorten the total examination time. If at 1.5T, some authors [ 15 , 16 ] have demonstrated that LV delineation remains accurate enough to correctly assess wall motion and LVEF, it has not yet been proven that b-TFE cine sequences obtained at 3T could be acquired after gadolinium injection, all the more since the difference in T1 between the blood pool and the myocardium is decreased when increasing the field strength [ 16 ]. If post-contrast is currently a common practice in many 1.5T CMR sites, its generalization to 3T sites is not yet supported by the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…However in clinical routine examination time is critical. To shorten the study duration standard cine steady-state free precession (SSFP) MRI imaging can be obtained after injection of contrast medium without loss of accuracy for regional and global LV ventricular function [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although extracellular contrast agents decrease the blood‐myocardium interface contrast in bSSFP images, in clinical practice bSSFP images are typically acquired following the application of extracellular contrast agents . This, however, results in suboptimal automatic myocardial segmentation as well as restricted visual functional assessment .…”
mentioning
confidence: 99%
“…6 As the T 2 /T 1 ratio is high for blood and low for myocardium, there is a high contrast between blood and myocardium, which not only enables automatic myocardial segmentation but is also essential for the application of sophisticated image postprocessing, eg, strain analysis with feature-tracking software. [7][8][9] Although extracellular contrast agents decrease the blood-myocardium interface contrast in bSSFP images, 10 in clinical practice bSSFP images are typically acquired following the application of extracellular contrast agents. 11 This, however, results in suboptimal automatic myocardial segmentation as well as restricted visual functional assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation